Standard of Living and Residence of Senior Citizens in Institutional Care - Bielak, Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The study presents the problem of an appropriate and comprehensive shaping of the living environment of senior citizens in institutional care, i.e. creation of a most accessible built environment for them. The currently prevailing conditions in Polish care institutions for senior citizens are continuously improving, however they do not completely fulfill modern requirements and European standards expected from such institutions. In order for such a facility to provide an appropriate living environment for senior citizens and function efficiently, they cannot be based only on precisely defined guidelines and design principles. They have to be based on knowledge concerning senior citizens, their problems, needs and expectations; they also have to take into account the results of qualitative research based on the principles of universal design and ergonomics.